GAME EDUKASI PENGENALAN PAHLAWAN NASIONAL BERBASIS ANDROID - Marcel Arjuan Setiawan; Achmad Zakki Falani (SPIRIT, 2021)
A hero is a title to a highly decorated person and contributes to an institution ora country and fight the colonization of the fallen on the battlefield for Indonesia's independence. There are still a lot of kids who are ignorant of the introduction of national heroes who have fought for the independence of the united republic of Indonesia, which should be introduced to the younger generation as the next Indonesian people since they started to sit in education. Therefore, with the problem of identifying heroes, it is necessary for a learning medium to utilize android based smartphone technology to identify national heroes such as the national hero's introduction puzzle game to be a convenient learning media for children to know about national heroes. The study was created using the unity 3d application, as for the data sources used by observation done by collecting data online using Google forms to find out the extent of children in knowing Indonesian heroes and how they responded to their knowledge of Indonesian heroes, and for an interactive learning play on children. Based on the response results from children, it is concluded that it makes a media study for the introduction of this android based national hero dap.Keywords : Android, Hero National, Unity 3D